Design and control of a hybrid water pumping system using energy management for sustainable agricultural irrigation: A case study of the Sidi Bouzid region in Tunisia - Amri, Akram; Moussa, Intissar; Khedher, Adel (Center of Biomass & Renewable Energy (CBIORE), 2025)
In this study, a renewable energy-powered Hybrid Water Pumping System (HWPS) is proposed for agricultural irrigation, designed to operate without reliance on battery storage. The system is adapted to the local climatic characteristics of the Sidi Bouzid region in Tunisia and is intended to regulate and coordinate water flow to effectively meet crop irrigation requirements. Hence, the system comprises three principal subsystems: A Wind Turbine (WT) driving a Doubly-Fed Induction Generator (DFIG) connected to the grid via rotor-side and grid-side converters; a Photovoltaic (PV) module integrated via a DC/DC boost converter; and a water pumping unit, consisting of an Induction Machine (IM) coupled to a centrifugal pump. The mathematical models of each subsystem were developed, and a control algorithms suite was implemented to enhance overall performance and energy efficiency. Maximum Power Point Tracking (MPPT) techniques were employed to optimize the energy harvested from renewable sources. A non-linear Sliding Mode Control (SMC) strategy was implemented to manage the DFIG power output, while Input-Output Feedback Linearization (IOFL) was applied to control the IM via a Voltage Source Inverter (VSI).Since the system operates without battery storage, a dynamic Energy Management System (EMS) is investigated to ensure optimal energy distribution, prioritizing solar energy during peak sunlight hours and transitioning to wind energy when solar availability declines. Simulation results validate the system’s effectiveness and demonstrate its potential for sustainable agricultural applications in rural areas. This approach offers a cost-effective and environmentally friendly sustainable solution for irrigation, contributing to improving water and energy security.